“PROSPECTS OF USING NANOMATERIALS IN ARCHITECTURE AND CONSTRUCTION” - Achilova , M. F. (Educational Research in Universal Sciences, 2023)
Our goal is to develop proposals for the further improvement of today’s architecture and to substantiate them scientifically. In the modernization of architectural complexes, it is about the creation of a unique project using nanotechnologies.